Bubble collapse near a fluid-fluid interface using the spectral element marker particle method with applications in bioengineering. (April 2017) - Rowlatt, Christopher F.; Lind, Steven J.
Highlights: Low inertia bubble collapse near a fluid-fluid interface is studied. Principal application is in bio-fluid mechanics, namely sonoporation. Newtonian and viscoelastic models of nearby cell are considered. Normal and shear stresses propagate through interior and along cell membrane. Propagation of stresses potential reason for non-localised cell membrane disruption. Abstract: The spectral element marker particle (SEMP) method is a high-order numerical scheme for modelling multiphase flow where the governing equations are discretised using the spectral element method and the (compressible) fluid phases are tracked using marker particles. Thus far, the method has been successfully applied to two-phase problems involving the collapse of a two-dimensional bubble in the vicinity of a rigid wall. In this article, the SEMP method is extended to include a third fluid phase before being applied to bubble collapse problems near a fluid-fluid interface. Two-phase bubble collapse near a rigid boundary (where a highly viscous third phase approximates the rigid boundary) is considered as validation of the method. A range of fluid parameter values and geometric configurations are studied before a bioengineering application is considered. A simplified model of (micro)bubble-cell interaction is presented, with the aim of gaining initial insights into the flow mechanisms behind sonoporation and microbubble-enhanced targeted drug delivery. Results from this model indicate that the non-local cell membrane distortion (blebbing) phenomenon often observed experimentally may result from stress propagation along the cell surface and so be hydrodynamical in origin.